Fabrication and characteristics of polyethylene glyco/cotton friction spun composite yarn. (April 2022) - Yu, Lixiang; Ke, Guizhen; Wang, Yu; Tang, Jiani
Highlights: Friction spinning was successfully applied in the fabrication of form-stable phase change composite materials. Polyethylene glycol was coated on yarns through sizing method to achieve continuous preparation and large-scale production. The latent heat of the composite yarns can reach 114.33 J/g. The latent heat of the composite yarns can reach 114.33 J/g. Abstract: This paper focused on the preparation and performance analysis of a series of friction-spun composite yarns with phase change function. We firstly prepared a core yarn (polyethylene glycol/cotton) through sizing method, and then made seven composite yarns with different sheath materials and spinning drums speeds by friction spinning. Finally, the study explored the effects of spinning drums speeds and sheath fibers on morphology, yarn strength, and thermal properties of friction-spun composite yarns. The yarns whose shell material is terylene and spinning drums speed is 8000 r/min or 9000 r/min were optimized. The results show that terylene/polyethylene glycol/cotton yarn has the tightest wrapping state, while wool/polyethylene glycol/cotton has the loosest wrapping state. Besides, yarn strength increases by 66% after sizing PEG. The enthalpy efficiency of the yarn reaches up to 56%, whose melt peak is at 59.58 °C and the corresponding latent heat is 114.33 J/g. Such a structure and manufacture method make it easy to replace the raw materials in the yarn, so the temperature and thermal storage property of the yarn is adjustable, suggesting great potential for application in energy storage and thermo-regulation products.